Sporulation Of Arbuscular Mycorrhizal Fungus, Glomus Intraradices, Through Root Organ Culture (Applied Biological Research, 2015)
This study reports the cultivation of arbuscular mycorrhiza (AM), Glomus  intraradices spores in Ri-TDNA transformed carrot (Daucus carota) roots  using Agrobacterium rhizogenes MTCC culture 532. The germination and  mass multiplication of surface sterilized AM spores was studied at  different pH levels, sucrose concentrations and inoculumssources. The  multiplication of AM spores were successfully established using dual  culture technique in modified Strullu and Romands medium amended  with 1.0% sucrose at pH 5.5 and incubation temperature of 27°C under  condition. The influence of using different inoculum sources such as  bunch of spores, infected root bits and spore gel/ agar plug of G.  intraradices in root organ culture were evaluated during successive  generations under in vitro conditions. Among these, agar plug with high  density of viable spores (initially 50) along with few mycorrhized root  apexes guarante
Keywords: Agrobacterium rhizogenes; AM spores; Daucus carota; Glomus intraradices; mass multiplication; root organ culture